Promising approaches to address the needs of poor female farmers: Resources, constraints, and interventions - Quisumbing, Agnes R.; Pandolfelli, Lauren (International Food Policy Research Institute, 2009)
Recognizing that “gender matters,” many development interventions have aimed to close the gender gap in access to resources, both human and physical, and to address the specific needs of female farmers. This paper critically reviews attempts to increase poor female farmers’ access to, and control of, productive resources in Sub-Saharan Africa and South Asia. It surveys the literature from 1998 to 2008 that describes interventions and policy changes across several key agricultural resources, including land, soil, and water; labor-saving technologies; improved varieties; extension services; and credit. Compared with interventions designed to increase investment in human capital, only a minority of interventions or policy changes designed to increase female farmers’ access to productive resources have been rigorously evaluated. Future interventions need to consider interactions among inputs rather than treat each input in isolation, adapt interventions to clients’ needs, and pay attention to the design of alternative delivery mechanisms, the trade-offs between practical and strategic gender needs, and the culture and context specificity of gender roles.